2015
DOI: 10.3109/0284186x.2015.1046997
|View full text |Cite|
|
Sign up to set email alerts
|

Methodology for adaptive and robust FDG-PET escalated dose painting by numbers in head and neck tumors

Abstract: Objective. To develop a methodology for using FDG PET/CT in adaptive dose painting by numbers (DPBN) in head and neck squamous cell carcinoma (HNSCC) patients. Issues related to noise in PET and treatment robustness against geometric errors are addressed. Methods. Five patients with locally advanced HNSCC scheduled for chemo-radiotherapy were imaged with FDG-PET/ CT at baseline and 2-3 times during radiotherapy (RT). The GTV PET was segmented with a gradient-based method. A double median filter reduces the imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…PET). Dose painting enables mapping of dose prescription to non-uniform distribution of metabolic, biochemical, and molecular abnormalities within the tumor [1820]. FDG-PET/CT is increasingly used in dose painting for NPC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PET). Dose painting enables mapping of dose prescription to non-uniform distribution of metabolic, biochemical, and molecular abnormalities within the tumor [1820]. FDG-PET/CT is increasingly used in dose painting for NPC.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, FDG-PET directed dose distribution could lead to better sparing of organs at risk, such as parotid glands [22, 23]. Various PET-based threshold methods have been proposed for target volume delineation, including SUV2.5, SUV50%max, and signal/background ratio (SBR) [9, 22, 24, 25]. In this study, SUV50%max target was selected as the clinical standard for dose escalation.…”
Section: Discussionmentioning
confidence: 99%
“…In RT, PET image registration is used for the following purposes among others: (a) better tumor target definition; (b) propagation of contours from one image set to another; (c) adaptive therapy planning/dose painting to selectively increase dose to more PET‐avid target regions; and (d) incorporation of respiratory‐gated PET information in treatment planning . The reader is referred to AAPM Task Group 132 (TG‐132: Use of Image Registration and Fusion Algorithms and Techniques in Radiotherapy), which deals with the topic of image registration in RT.…”
Section: Current Usage Of [18f]fdg‐pet In Rtmentioning
confidence: 99%
“…(c) adaptive therapy planning/dose painting to selectively increase dose to more PET-avid target regions [94][95][96] ; and (d) incorporation of respiratory-gated PET information in treatment planning. [97][98][99] The reader is referred to AAPM Task Group 132 (TG-132: Use of Image Registration and Fusion Algorithms and Techniques in Radiotherapy), 100 which deals with the topic of image registration in RT.…”
Section: C3 Image Registrationmentioning
confidence: 99%
“…For Differding et al (66) a decrease of target volumes can be shown in the first radiation treatment week. However, replanning is considered optimal after two treatment weeks but no later due to increasing edema and inflammation and the consequent difficult to distinguish boundaries.…”
Section: Art and Dose Painting Techniquementioning
confidence: 93%